DUETTE: a phase II randomized, multicenter study to investigate the efficacy and tolerability of a second maintenance treatment in patients with platinum-sensitive relapsed epithelial ovarian cancer, who have previously received poly(ADP-ribose) polymerase (PARP) inhibitor maintenance treatment. Issue 11 (2nd September 2020) - McMullen, Michelle; Karakasis, Katherine; Loembe, Bienvenu; Dean, Emma; Parr, Graem; Oza, Amit M
Abstract : Background: With the success of poly(ADP-ribose) polymerase (PARP) inhibitor therapy in the first-line and second-line treatment settings, a new patient population is emerging with platinum-sensitive relapsed ovarian cancer, who have previously received a PARP inhibitor in the maintenance setting and for whom no second maintenance standard of care exists. DUETTE (NCT04239014 ) will evaluate the combination of ceralasertib (a potent, selective inhibitor of the serine/threonine kinase ataxia telangiectasia and Rad3-related protein (ATR) + olaparib, or olaparib monotherapy, compared with placebo, in this patient population of unmet need. Primary Objective: The primary objective is to assess the efficacy of ceralasertib + olaparib combination, and olaparib monotherapy, compared with placebo, as second maintenance therapy in platinum-sensitive relapsed ovarian cancer. Study Hypothesis: This study will test the hypothesis that ceralasertib + olaparib, or olaparib monotherapy, is tolerable, and effective at prolonging progression-free survival compared with placebo. Trial Design: This is a phase II, multicenter study where patients will be randomized in a 1:1:1 ratio to receive either (Arm 1) ceralasertib + olaparib, (Arm 2) olaparib monotherapy, or (Arm 3) placebo. The olaparib and placebo arms will be double-blinded, whereas the ceralasertib + olaparib arm will be open label. Patients will be stratified according to BRCA status, and response to platinum-based chemotherapy. Major Inclusion/Exclusion Criteria: Eligible patients will have histologically diagnosed high-grade epithelial ovarian cancer, with platinum-sensitive relapse on, or after, completion of at least 6 months of any prior PARP inhibitor maintenance therapy (a minimum of 12 months is required if the patient received PARP inhibitor maintenance following first-line chemotherapy). If the prior PARP inhibitor used was olaparib then patients must have received treatment without significant toxicity or the need for a permanent dose reduction. Disease relapse in the second-line or third-line setting is allowed. Patients who have received secondary debulking surgery are potentially eligible if they meet all other inclusion criteria. Primary Endpoints: The primary endpoint is progression-free survival determined by blinded independent central review according to RECIST 1.1, with sensitivity analysis of progression-free survival using investigator assessments according to RECIST 1.1. Sample Size: 192 patients. Estimated Dates for Completing Accrual and Presenting Results: December 2022. Trial Registration: NCT04239014 .